An All‐Solid‐State Flexible Piezoelectric High‐k Film Functioning as Both a Generator and In Situ Storage Unit. (15th October 2015) - Tong, Wangshu; Zhang, Yihe; Zhang, Qian; Luan, Xinglong; Lv, Fengzhu; Liu, Leipeng; An, Qi
Abstract : An all‐solid‐state flexible generator–capacitor polymer composite film converts low‐frequency biomechanical energy into stored electric energy. This design, which combines the functionality of a generator with a capacitor, is realized by employing poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) in the simultaneous dual role of piezoelectric generator and polymer matrices of the flexible capacitor. Proper surface modification of the reduced graphene oxide (rGO) fillers in the polymeric matrices is indispensable in achieving the superior energy storage performance of the composite film. The heightened dielectric performance stems from enhanced compatibility of the rGO fillers and PVDF‐HFP matrices, and a microcapacitor model properly explains the dielectric behaviors. A device that is easily fabricated using our film allows timely decoupled motion energy harvest and output of the motion‐generated electricity. This report opens new design possibilities in the fields of motion sensors, information storage and high‐voltage output by accumulating low‐frequency random biological motions. Abstract : An all‐solid‐state flexible generator–capacitor film is fabricated by employing the dual role of PVDF‐HFP: it serves as both the piezoelectric generator and the polymeric matrix of the capacitor. Chemically modified reduced graphene oxide fillers effectively enhance film permittivity. The film converts low‐frequency biomechanical energy to stored electricity and can delayed release the electric signal on demand.